Raising fund for waqf land development via Islamic Real Estate Investment Trust (iREIT) - Che Embi, Nor Azizan; Ramlee, Roslily (Institut Kajian Zakat Malaysia, UiTM, 2013)
This paper attempts to explore the possibility of using Islamic REITs (iREITs) as one of the potential financing method for waqf land development. This paper identifies several ways on how iREITs issuance can be use to tap money from the generous Muslim donors and the investors for the development. The funds raised by the issuance of iREITs not only meant to finance the initial stage of waqf land development but are also expected to generate continuous cash inflows to the State Religious council. The paper aims to focus on the sustainability of the funds that can be used to finance the development of waqf land.